INSTAGRAM AS A DA'WAH MEDIA (ANALYSIS OF THE CONTENTS OF NING SHAILA HASINA'S DA'WAH MESSAGES) - Firdausiyah, Rofiqotul Afifah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The availability of several social media facilities that are very popular with teenagers unknowingly becomes a threat and damage if it is not accompanied by self- and emotional control as well as directions and advice from other people who have qualified knowledge. However, in this millennial era it is very difficult to gather teenagers in an Islamic study or da'wa. For this reason, it is important for the accusers to enter the modern, millennial world and use social media such as Instagram, Tik Tok, Twitter and so on.This study aims to examine the